Bupropion for adults with attention-deficit hyperactivity disorder: meta-analysis of randomized, placebo-controlled trials - Maneeton N. (2014)
Aim: The aim of this study was to systematically review the efficacy, acceptability and tolerability of bupropion in comparison to placebo. Only randomized-controlled trials were included in the meta-analysis. Methods: MEDLINE, EMBASE, CINHL, PsycINFO and Cochrane Controlled Trials Register were searched in October 2010. Study populations comprised adults with any subtype of attention-deficit hyperactivity disorder, attention-deficit disorder, hyperkinetic disorder, minimal brain dysfunction, minimal cerebral dysfunction or minor cerebral dysfunction. Efficacy outcomes were pooled mean changed scores of the ADHD rating scale (ADHD-RS) and the overall response rates. The overall discontinuation rate was considered as the measure of acceptability. Results: A total of 349 participants (n for bupropion treatment = 175) in five published randomized, controlled trials were included. Bupropion sustained- or extended-release was the experimental treatment in all studies. The pooled mean changed score of the ADHD-RS of the bupropion-treated group was greater than that of the placebo-treated group with a weighted mean difference (95%CI) of 5.08 (3.13-7.03). The overall response rate of the bupropion-treated group was significantly greater than that of placebo-treated groups with a relative risk (95%CI) of 1.67 (1.23-2.26). However, the pooled overall discontinuation rate and the pooled discontinuation rate due to adverse events were not significantly different between groups with a relative risk (95%CI) of 1.11 (0.71-1.72) and 0.87 (0.08-9.79), respectively. Conclusion: The evidence suggests that bupropion is superior to placebo and effective for the treatment of ADHD in adults. However, its acceptability and tolerability were not significantly higher than those of placebo. © 2011 Japanese Society of Psychiatry and Neurology.